2007
DOI: 10.1007/s11661-007-9189-3
|View full text |Cite
|
Sign up to set email alerts
|

Grain Growth in Cryomilled Ni Powder during Degassing

Abstract: Grain growth during the degassing of Ni cryomilled in liquid nitrogen and that cryomilled in liquid argon was investigated by X-ray diffraction (XRD) and confirmed by transmission electron microscopy (TEM) studies. The Ni cryomilled in liquid argon was found to have significantly more thermal stability than the Ni cryomilled in liquid nitrogen, with grain sizes of 28 and 62 nm, respectively, after 32 hours of degassing at 723 K. The Ni cryomilled in liquid argon was found to have significantly greater amounts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…[32] Nanocrystalline Ni powders with a grain size of approximately 10 nm were prepared by cryomilling commercially pure Ni powders (>99.7 wt %) in liquid nitrogen. [33] The cryomilled Ni powders were placed in stainless steel can and degassed, first at a temperature of 450 8C for 24 hours followed by a second degassing step at a temperature of 810 8C for 2.5 hours. The degassed cans were then QI forged at 800 8C to form bulk dense NS Ni with a purity of 99.3% (Supporting Information Tables 1 and 2), a density of 8.87 g cm À3 (99.6% of Ni's theoretical density), and a multimodal grain size distribution.…”
mentioning
confidence: 99%
“…[32] Nanocrystalline Ni powders with a grain size of approximately 10 nm were prepared by cryomilling commercially pure Ni powders (>99.7 wt %) in liquid nitrogen. [33] The cryomilled Ni powders were placed in stainless steel can and degassed, first at a temperature of 450 8C for 24 hours followed by a second degassing step at a temperature of 810 8C for 2.5 hours. The degassed cans were then QI forged at 800 8C to form bulk dense NS Ni with a purity of 99.3% (Supporting Information Tables 1 and 2), a density of 8.87 g cm À3 (99.6% of Ni's theoretical density), and a multimodal grain size distribution.…”
mentioning
confidence: 99%
“…A bulk NS Ni sample with porosity and N segregated on the GBs was prepared by cyomilling and quasi-isostatic (QI) forging [27,28]. Nanocrystalline Ni powders with a grain size of approximately 10 nm were prepared by cryomilling commercially pure Ni powders (>99.7 wt.%) in liquid argon.…”
Section: Methodsmentioning
confidence: 99%
“…Chemical composition analysis and density measurement indicate that the forged NS Ni has a purity of 99.2% and a density of 8.51 g/cm 3 (95.5% of Ni theoretical density). The principal impurities are N, Fe and C, which originate from the milling media [27,28], as listed in Table 1. A portion of the forged disk (with a thickness of 10 mm and a diameter of 50 mm) was rolled in thickness reduction of 20% with the rolling direction normal to the forging direction.…”
Section: Methodsmentioning
confidence: 99%
“…As can be seen, only pure Si peaks are detected both before and after cryomilling. In contrast, the iron (Fe) content is surprisingly low, in comparison to that generated from the cryomilling of other materials [25,26]. Grain size calculation results determined by full width at half maximum (FWHM) show that the grain size of Si decreases from 125 nm to 25 nm as cyomilling time increases from 6 h to 24 h. Thus, it is suggested that the grain size of the nanocrystalline Si can be well controlled by adjusting the cryomilling time.…”
Section: Controlled Grain Size Of the Cryomilled Nanocrystalline Si Pmentioning
confidence: 99%